Physiological Activity of Campylobacter jejuni Far below the Minimal Growth Temperature - Hazeleger, Wilma C. (American Society for Microbiology, 1998)
The behavior of Campylobacter jejuni at environmental temperatures was examined by determining the physiological activities of this human pathogen. The minimal growth temperatures were found to be 32 and 31°C for strains 104 and ATCC 33560, respectively. Both strains exhibited a sudden decrease in growth rate from the maximum to zero within a few degrees not only near the maximal growth temperature but also near the minimal growth temperature. This could be an indication that a temperature-dependent transition in the structure of a key enzyme(s) or regulatory compound(s) determines the minimal growth temperature. Oxygen consumption, catalase activity, ATP generation, and protein synthesis were observed at temperatures as low as 4°C, indicating that vital cellular processes were still functioning. PCR analysis showed that cold shock protein genes, which play a role in low-temperature adaptation in many bacteria, are not present in C. jejuni. The fact that chemotaxis and aerotaxis could be observed at all temperatures shows that the pathogen is able to move to favorable places at environmental temperatures, which may have significant implications for the survival of C. jejuni in the environment.